Pembentukan Karakter Melalui Kegiatan OSWA Ponpes Tarbiyah Islamiyyah At-Taqwa Canduang - Fatimah Khairani; Irfan Fauzi; Fenny Ayu Monia (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Education is not enough just to make children smart, but it must be able to create noble values or national character. Therefore, instilling noble values or character must start from an early age so that later they will be able to become proud children of the nation. Facing the problem of declining morals or character in children at school, innovations are needed to shape character in children in order to reduce various moral crises. Character formation of students at school can be carried out through activities at school. Activities at school can be carried out through various routine and spontaneous activities to shape children into positive or good behavioral values. This research aims to explore and examine information about character formation through OSWA activities in schools carried out at the Tarbiyah Islamiyyah At-Taqwa Canduang Islamic Boarding School. This research approach is qualitative with a case study method, to reveal and understand the realities that occur intensively and in depth regarding the above phenomena. Data and information collection techniques were carried out through interviews, participant and non-participant observation, documentation studies, and literature studies. The findings of this research are that the relationship between morning da'wah activities and character education is that it is a manifestation of the knowledge gained in class with the attitudes and skills that must be developed so that students can possess them in the form of noble moral values which have become a culture in the school's social life.